Extant diversity and estimated number of Gracillariidae (Lepidoptera) species yet to be discovered in the Neotropical region - Brito,Rosângela (2016)
ABSTRACT Gracillariidae (Lepidoptera) are commonly known by the leaf miner habit found in the larval stage of most species. By using worldwide, public databases on species diversity and DNA sequences available for extant gracillariid species, we determined changes in the rate of taxonomic species descriptions through time, mapped their spatial distributions, examined their phylogenetic diversification, and estimated the number of species yet to be described for the family in the Neotropics. We recovered 185 species, a number that is smaller than that found in any other biogeographic region. However, it was estimated that at least 3875 additional species remain to be described in the region. Phylogenetic diversification showed a pattern of expanding diversity. A few entomologists have been involved with gracillariid taxonomy in the Neotropics, having 39% of the species been described by a single taxonomist. In most of such cases, descriptions were based on the adults only. A few species have been described from biomes known to have some of the greatest diversity on earth, such as the Atlantic Forest. Thus, such a scenario results from low sampling and scarce taxonomic activity that has prevailed for this family of moths in the Neotropics. It may also be associated with their small body size and to the fact that gracillariids do not seem to be attracted to light traps as much as other moths, which make their collection and identification by non experts difficult. We also suggested scientific and political actions that could be adopted to overcome such an unfavorable scenario.